Let's talk about it : turning confrontation into collaboration at work - Marciano, Paul L. (McGraw Hill, 2021)
"The bestselling author of Carrots and Sticks Don't Work shares his proven conversational techniques for turning workplace confrontations into respectful, successful collaborations. In the workplace, the most common approach to dealing with what we believe will be a difficult or emotionally charged conversation with our bosses, colleagues, or direct reports is, simply, not to. Most of us will do anything to avoid conflict, but the confrontations we try to avoid usually end up doing more harm to our relationships and costing more time, money, and aggravation. In Let's Talk About It, bestselling author and top consultant Paul Marciano presents a powerful collection of proven communication and relationship strategies-inspired by the author's acclaimed RESPECT model of employee engagement-that will show us how to: Recognize and let go of the unconscious cognitive biases that keep us from seeing things from other people's perspectives Negotiate the minefields and goldmines of language, both verbal and nonverbal Understand that what we say to ourselves is as important as what we say to others Work with different personality types, and use simple conversational techniques to resolve conflicts and improve collaborations Conduct these difficult conversations both in person and in virtual environments Filled with ready-to-use sample scripts, real-world scenarios of common workplace disagreements, and proven psychological methods for diffusing conflicts effectively, Let's Talk About It will help you master the necessary communication skills to deal with the most challenging people and situations confidently and competently. It will enable you to turn any confrontation into a successful collaboration"--